The uncertainty about the social cost of carbon: A decomposition analysis using FUND - David Anthoff; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
We report the results of an uncertainty decomposition analysis of the social cost of carbon as estimated by FUND, a model that has a more detailed representation of the economic impact of climate change than any other model. Some of the parameters particularly influence impacts in the short run whereas other parameters are important in the long run. Some parameters are influential in some regions only. Some parameters are known reasonably well, but others are not. Ethical values, such as the pure rate of time preference and the rate of risk aversion, therefore affect not only the social cost of carbon, but also the importance of the parameters that determine its value. Some parameters, however, are consistently important: cooling energy demand, migration, climate sensitivity, and agriculture. The last two are subject to a large research effort, but the first two are not.
Keywords: 330; social cost of carbon; uncertainty; research priorities; Umweltbelastung; Treibhausgas-Emissionen; Soziale Kosten; Internationale Wanderung; Agrarproduktion; Theorie